1984
DOI: 10.1042/bj2200773
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ovine rhodopsin. Identification of the phosphorylated sites

Abstract: Light-dependent phosphorylation of sheep opsin was obtained in purified discs to which was added a partially purified preparation of rhodopsin kinase. A maximum ratio of 1.8 mol of phosphate/mol of rhodopsin bleached was obtained. Perturbing the lipid bilayer did not alter the phosphorylation ratio. Dephosphorylation in both segments and discs was only achieved when the supernatant fraction from a retina homogenate was added. Complete dephosphorylation required the presence of the detergent dodecyltrimethylamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…The presence of a variety of kinases in ROS, such as RK, PKC, and PKA, has been previously reported ( 93,(141)(142)(143). It was demonstrated that ROS PLD is activated by PKC ( 82 ).…”
Section: Pldmentioning
confidence: 99%
“…The presence of a variety of kinases in ROS, such as RK, PKC, and PKA, has been previously reported ( 93,(141)(142)(143). It was demonstrated that ROS PLD is activated by PKC ( 82 ).…”
Section: Pldmentioning
confidence: 99%
“…As a consequence, the previously available direct protein analyses of membrane receptors were generally limited to proteins that were readily available in larger quantities. Apart from pioneering work on rhodopsin (11,12), there are only a very few scattered reports in the literature on direct observation of post-translational modifications of G-protein-coupled membrane receptors (13)(14)(15). The present results indicate that with the development of new methods for rapid, mild isolation of as little as 1-2 pmol of membrane receptors on gels and the combination of highly sensitive MALDI and electrospray ion trap mass spectrometry, direct evaluation of the sites and types of post-translational modifications of membrane receptors is poised to become a routine characterization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition it has been presumed that ET receptors are post-translationally modified by glycosylation of the NH 2 terminus and by phosphorylation and palmitoylation of the cytoplasmic surface. Based on homology with other G-protein-coupled receptors (8 -10), there has been speculation regarding possible structures, functional regions, and sites of post-translational modifications for endothelin receptors (11)(12)(13)(14)(15)(16). However, as yet there is very little direct evidence for attributes such as the sites and the roles of glycosylation, palmitoylation, and phosphorylation, the location of the endothelin-binding site and the basis for discrimination among the three different endothelin isoforms.…”
mentioning
confidence: 99%
“…The enzyme responsible for this activity, rhodopsin kinase, utilizes only the photoactivated form of rhodopsin as a substrate (Weller et al, 1975;Frank & Buzney, 1975;Kuhn, 1978;Shichi & Somers, 1978). Protein mapping studies indicated that rhodopsin is phosphorylated at multiple serine and threonine sites clustered in the C-terminus Barclay & Findlay, 1984;Thompson & Findlay, 1984); up to 9 mol of phosphate have been reported per mol of pigment (Wilden & Kuhn, 1982). Phosphorylation of rhodopsin has been proposed to have a signal-terminating function; this was suggested when it was found that addition of ATP to rod outer segments attenuated the activation ofcyclic GMP phosphodiesterase in this system (Liebman & Pugh, 1980).…”
Section: Muscarinic Acetylcholine Receptors Several Studies Havementioning
confidence: 99%